2023
DOI: 10.1093/cercor/bhad447
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable contributions of the hippocampus and orbitofrontal cortex to representing task space in a social context

Jiajun Liao,
Jinhui Li,
Yidan Qiu
et al.

Abstract: The hippocampus (HC) and the orbitofrontal cortex (OFC) jointly encode a map-like representation of a task space to guide behavior. It remains unclear how the OFC and HC interact in encoding this map-like representation, though previous studies indicated that both regions have different functions. We acquired the functional magnetic resonance imaging data under a social navigation task in which participants interacted with characters in a two-dimensional “social space.” We calculate the social relationships be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Our results indicated that the HIP may be responsible for updating the map of spaces and the OFC for utilizing the map to make inferences. In our recent study 72 , we also found that the HIP was involved in collecting and updating information, whereas the OFC was associated with the relationships between agents in the environment.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Our results indicated that the HIP may be responsible for updating the map of spaces and the OFC for utilizing the map to make inferences. In our recent study 72 , we also found that the HIP was involved in collecting and updating information, whereas the OFC was associated with the relationships between agents in the environment.…”
Section: Discussionmentioning
confidence: 78%
“…These results indicated that these two regions may adopt different roles in forming and representing a cognitive map. Previous studies suggested that the HIP and OFC are involved in different aspects of a cognitive map 29 , 72 , 73 . Our results indicated that the HIP may be responsible for updating the map of spaces and the OFC for utilizing the map to make inferences.…”
Section: Discussionmentioning
confidence: 99%
“…The cerebral cortex and hippocampus are essential for higher cognitive functions such as memory, learning and navigation [1]. Pyramidal neurons, as the fundamental computational units in these brain structures, possess intricate dendritic morphologies and diverse ion channels, making them a primary focus in neuroscience research [2].…”
Section: Introductionmentioning
confidence: 99%